Modeling thermophysical processes in a nuclear reactor on fast neutrons - Berezovskaya, I.E.; Vityuk, G.A.; Toleubekov, K.O. (Recent Contributions to Physics, 2019)
The development of reactors on the fast neutrons and nuclear power engineering is generally responsible for its formation. One of them is that the responsibility for the reliability of the reactor equipment, its calculation, creation and operation sharply increases. For the development of projects in the field of nuclear energy, it is necessary to carry out various thermalhydraulic calculations. Using the results of calculations will allow for timely adjustment in the engineering. This work is devoted to the study of the processes of hydrodynamics and heat exchange of reactor on fast neutrons with an electrical power of 600 MW with a volumetric energy release up to 0.494 GW / m3. In the process of work, 3D model of the selected fuel assembly area was created in the program Gambit. Computer modeling was carried out in the ANSYS FLUENT software package as a result of which thermal state of fuel assembly for established mode of heat transfer was defined. The calculations were carried out using the k-ε coolant motion turbulent model. This article presents the results of calculations on hydrodynamics and heat transfer in a segment of the selected fuel assembly of a fast sodium reactor. The non-uniformity of temperature distributions along the height of the active zone in various areas of fuel assemblies, the distribution of the heat carrier velocity, as well as pressure indicators are shown. The analysis of the results obtained shows that the temperatures of the structural elements do not exceed the permissible temperatures; the pressure drop is significantly lower than in reactors of another type.